A case report of desmoid type fibromatosis of the breast - Pankratjevaitė, Lina; Ceslevičienė, Ieva; Poškienė, Lina; Boguševičius, Algirdas (Lietuvos chirurgija, 2019)
Background. Desmoid type fibromatosis of the breast is a rare fibroblastic proliferative disease. It may be sporadic or associated with trauma, Gardner’s syndrome, etc. Desmoid tumour of the breast is a benign, locally aggressive disease. However, it does not metastasize. Case report. We report a case of a 65-year-old woman with right breast desmoid type fibromatosis. Conclusions. Diagnosis of breast desmoid tumour is difficult: clinically and radiologically it may mimic carcinoma. Definitive diagnosis is proved just by histopathological examination results. First choice treatment of breast fibromatosis is a radical surgical excision.
Keywords: breast fibromatosis; extraabdominal desmoid tumour; rare breast disease